Tax Implications of Relocation Across Local Work Regions in Sweden - Lidström,Ellen (2025)
This paper examines relocation of taxpayers during 2000 to 2021 across Swedish local work regions and its implications on the tax system. There exist 290 mu- nicipalities in Sweden, which are divided into 67 local work regions. Relocation is categorised as either relocation within or outside local work regions. Furthermore, a distinction is made between age and income groups in order to capture poten- tial differences in relocation patterns. With a Difference-in-Differences model the treatment effect of relocating in 2020 on local tax rate is derived. Findings show an increase of relocation growth within local work regions compared to outside local work regions, predominantly driven by 30 to 44 year olds and the middle- and high income groups. Local tax rate changes depend on relocation within or outside work regions, where within observes reductions and outside increases. The analysis con- tributes to how the modern economy challenges the present taxation system, and discusses potential adjustments.
Keywords: Relocation · Work Regions · Local Tax Rate · The Swedish Welfare State · Difference-in-Differences · Taxation System